Epigraphy Evidences of Sangam Literature (A Gleaned from Archeological Evidences) - Gajalakshmi, S; Sridhar, S (Sakha: Multidisciplinary Journal of Science, Art & Technology, 2025)
In view of the above mentioned extensiveness we have to undertake a variegated enquiry and search for corroborative evi-dences from other disciplines as well to determine the dates of various sangam works. The sources that could be tapped use-fully in this regard are enlisted hereunder literature Epicgraphy  foreignchronicles archaeological evidence someone literatures written to the Ramayana the most powerful literature by the Valmiki and arthashastra written by kaudilya and also edicts of Ashoka hathikumbha  inscription of caravela and Tamil inscriptions accounts of magasthani Though this work is assignable to 7th cent. A.D., the commentator of the work Nakkirar refers to the history of Muchchangam  the three Tamil Academies.
Keywords: Silappadikaram Arthshasthiram; Iraiyanar; Kalaiyalurai; Inscription; Kabadapuram